Validation of the Kaba Volcanic Eruption Disaster Mitigation E-Module as a Learning Media on Volcano Materials - Purwaningsih; Johan, Henny; Mayub, Afrizal (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
Indonesia is on the path of the